Exploring Students’ Mathematical Literacy Based on Mastery of Prerequisite Material - Hamda; Faisal, Ahmad; Alimuddin; Naufal, Muhammad Ammar; Hassan, Muhammad Nasiru (LPPM Undiksha, 2025)
Mathematical literacy is essential for students to apply mathematical reasoning in real-world contexts, yet its development often relies on foundational knowledge. Understanding how the mastery of prerequisite knowledge influences mathematical literacy can help formulate more effective teaching strategies. This study explores the relationship between students' mathematical literacy levels and their mastery of prerequisite knowledge in grade XI of high school. This study used a qualitative approach, five students were selected based on their mastery of prerequisite knowledge and mathematical literacy. Data were collected through tests and interviews, with methodological triangulation to ensure validity. The study's findings showed varying literacy outcomes according to mastery of prerequisites. Students with high-medium ability demonstrated competence in fairly complex tasks but struggled with advanced reasoning. In contrast, students with medium-high abilities could interpret and apply information well but faced challenges in solving high-level problems. This study suggests that the development of mathematical literacy is not always linear with the mastery of prerequisites, highlighting the importance of teaching strategies that integrate conceptual understanding with literacy skills. These insights contribute to mathematics education by emphasizing the role of foundational knowledge in improving students' mathematical literacy.